Qualitative analysis of 2019-nCoV mathematical model via an efficient computational technique. Issue 2 (17th February 2021) - Devi, Anju; Jakhar, Manjeet; Singh, Yudhveer
Abstract: In the present scenario, the whole world struggling with Corona Virus Disease (COVID-19) which is a extremely transmittable disease stimulate by the novel corona virus (2019-nCoV) that believed to be originated in Wuhan, central China. Here, a mathematical analysis of 2019-nCoV mathematical model is considered with Caputo fractional order derivative operator. This model is made up of six subclasses i.e. susceptible people, exposed people, infected people, asymptotically infected people, recovered people and reservoir people. Authors obtained the series solutions of each subclasses of the proposed mathematical model via Sumudu Transform Homotopy Perturbation Method (STHPM). The results that have come are correct to show these authors have provided graphical interpretations.